A mechanically adaptive polymer based triboelectric nanogenerator for long-life self-powered wearable electronics. (20th April 2023) - Wang, Shuo; Li, Qingye; Wang, Su; Zhang, Wei; Lu, Canhui; He, Xu
Graphical abstract: Highlights: Mechanically adaptive PBS was synthesized and incorporated in stretchable TENG. Superior to conventional self-healing elastomers, PBS has an additional high impact property due to the dynamic crosslink in its supramolecular structure. The excellent impact resistance ensured the safe operation/enhanced lifetime of the ma-TENG against strong impact. The ma-TENG can be electrically integrated as sustainable power source and self-powered sensor for wearable electronics. Abstract: Safe operation under the mechanical impact represents one necessary demand for long-term wearable electronics. However, the incorporation of mechanically adaptive material into electronic devices is limited due to the lack of suitable material with a feasible design. Here, we developed a viscoelastic Polyborosiloxane (PBS) based mechanically adaptive triboelectric nanogenerator (ma-TENG) via a one-structure stretchable fiber strategy. Compared with conventional stretchable/self-healable elastomers, the synthesized PBS has an additional high-impact resistant property. The evolution of the dynamic boron/oxygen dative bonds in the supramolecular chains was investigated in situ by a 2D-FTIR method. The impact energy dissipation reached as high as 79.1 %, and 43.6 % can be retained at the high-impact rate. By incorporating PBS into the fully stretchable design, the ma-TENG maintained good output when stretched up to 70%, which was stable with negligible output attenuation after 10, 800 cycles of strong impact during operation. The ma-TENG can be electrically integrated for powering portable electronics. Moreover, mechanical adaptability of the ma-TENG made it excellent for self-powered pressure sensing with good linearity. This work provides a universal strategy to develop ma-TENG with extra protection and enhanced lifetime, which will be an enlighten for constructing next-generation mechanically adaptive electronics.